2012
DOI: 10.1038/nn.3267
|View full text |Cite
|
Sign up to set email alerts
|

Choice-related activity and correlated noise in subcortical vestibular neurons

Abstract: Functional links between neuronal activity and perception are studied by examining trial-by-trial correlations (choice probabilities) between neural responses and perceptual decisions. We addressed fundamental issues regarding the nature and origin of choice probabilities by recording from subcortical (brainstem and cerebellar) neurons in rhesus monkeys during a vestibular heading discrimination task. Subcortical neurons showed robust choice probabilities that exceeded those seen in cortex (area MSTd) under id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
121
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(132 citation statements)
references
References 55 publications
10
121
1
Order By: Relevance
“…We have found that peripheral sensory fibers innervating the otolith organs have heading discrimination thresholds that are of similar magnitude to thresholds in the VN and CN (13), as well as to thresholds of cortical neurons (1-3). Despite having similar sensitivities, responses of otolith afferents do not correlate with perceptual decisions, whereas activity of central vestibular and cortical neurons does.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…We have found that peripheral sensory fibers innervating the otolith organs have heading discrimination thresholds that are of similar magnitude to thresholds in the VN and CN (13), as well as to thresholds of cortical neurons (1-3). Despite having similar sensitivities, responses of otolith afferents do not correlate with perceptual decisions, whereas activity of central vestibular and cortical neurons does.…”
Section: Discussionmentioning
confidence: 71%
“…Thresholds of VN/CN neurons have previously been shown to depend strongly on tuning curve slope (type II regression: r = −0.81, P = 3.4 × 10 −24 ) and weakly on median response variance (type II regression: r = 0.19, P = 0.07; Fig. 4 A and B, black symbols) (13). Similar relationships between neuronal threshold, tuning curve slope, and median response variance were found for our sample of otolith afferents (type II regression: r = −0.94, P = 2.7 × 10 −29 for tuning slope; r = −0.33, P = 0.01 for median response variance; Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations